The Hedonic and Arousal Affect Scale (HAAS): A brief adjective checklist to assess affect states. (June 2023) - Roca, Pablo; Vázquez, Carmelo; Ondé, Daniel
Abstract: The present study aims to develop a brief instrument to assess self-reported affective experiences, the Hedonic and Arousal Affect Scale (HAAS), rooted in the valence-arousal model of affect. Throughout four different studies, we found that: (1) the 12-item version showed a better goodness-of-fit than an initial longer version (Study 1; n = 259); (2) the two-dimensional model of affect (i.e., four-factor model: positive affect and high arousal, positive affect and low arousal, negative affect and high arousal, and negative affect and low arousal) showed the best fit to our data (Study 2; n = 525); (3) the HAAS showed evidence of concurrent validity with related measures in the field (Study 3; n = 480); and (4) it showed partial support for temporal invariance (Study 4; n = 262). The content and psychometric qualities of the HAAS make it a suitable brief scale to measure affect and could be particularly useful for repeated measures designs such as psychological interventions, experimental studies, or ecological momentary assessment studies. Highlights: Brief instrument (12 items) to assess self-reported affective experiences Rooted in the valence-arousal model of affect Concurrent validity with related measures and temporal invariance Useful for repeated measures designs (e.g. interventions, experimental, diary)